دور اليقظة الإستراتيجية في تبني التسويق الابتكاري دراسة حالة مؤسسة الذواقة الجزائرية –مداوروش سوق أهراس - شهيناز بلحسن; صفيا يلفوف (My University, 2021)
This study aims to highlight the role of strategic vigilance as an important strategic factor in adopting innovative marketing in the organization, which supports achieving excellence and strengthening its competitive position. To achieve this goal, this study was based on the descriptive approach, where a questionnaire was relied on to collect data, by selecting a sample. From the e ;ployees of the Algerian gourmet foundation in mdaourouche, as a case study. The sudy concluded that the institution under study depends to a large extent on the various types of strategic vigilance, as it was found that the latter has a signification impact on the adoption of innovative marketingwithin the institution, as the degree of dependence of the institution on strategic vigilance explains 70% of the variables that may accur in the organization. The level of innovative marketing for its employees, and the results also proved that the personal variables of the study sample did not have any significant effect on their answers. .................................................... تهدف هذه الدراسة إلى إبراز دور اليقظة الإستراتيجية كعامل استراتيجي مهم في تبني التسويق الابتكاري في المؤسسة، الذي يدعم تحقيق التميز وتدعيم الموقف التنافسي لها، ولتحقيق هذا الهدف تأسست هذه الدراسة على المنهج الوصفي، حيث تم الاعتماد على استمارة أسئلة لجمع البيانات، من خلال اختيار عينة من الموظفين في مؤسسة الذواقة الجزائرية بمداوروش، كحالة دراسية. وتوصلت الدراسة إلى أن المؤسسة محل الدراسة تعتمد بدرجة كب يرة على مختلف مجالات اليقظة الإستراتيجية، كما تبين أن لهذه الأخيرة اثر كبير في تبني التسويق الابتكاري داخل المؤسسة، حيث تفسر درجة اعتماد المؤسسة على اليقظة الإستراتيجية ما نسبته) 70.7 %( من المتغيرات التي قد تطرأ على مستوى التسويق الابتكاري للعاملين بها، كما أثبتت النتائج أن المتغيرات الشخصية لأفراد عينة الدراسة لم تكن لها أي اثر معنوي على إجاباتهم.